Developmental Defects in Trisomy 21 and Mouse Models - Jean Maurice Delabar; Revital Aflalo-Rattenbac; Nicole Créau (The Scientific World Journal)
Aneuploidies have diverse phenotypic consequences, ranging from mental retardation and developmental abnormalities to susceptibility to common phenotypes and various neoplasms. This review focuses on the developmental defects of murine models of a prototype human aneuploidy: trisomy 21 (Down syndrome, DS, T21). Murine models are clearly the best tool for dissecting the phenotypic consequences of imbalances that affect single genes or chromosome segments. Embryos can be studied freely in mice, making murine models particularly useful for the characterization of developmental abnormalities. This review describes the main phenotypic alterations occurring during the development of patients with T21 and the developmental abnormalities observed in mouse models, and investigates phenotypes common to both species.